Drivers of Telecommuting Policy in Nigerian Organisations - Koleayo Omoyajowo; Susan Ebosiem; Adeyemi Akinola; Sunday Amiolemen; Kolawole Omoyajowo; Andrew Oriola; Olapeju Adenekan; Aziba-anyam Gift Raimi (Garuda Prestasi Nusantara Consulting, 2021)
This study evaluates factors influencing the adoption of telecommuting among the selected organisations in Nigeria. A questionnaire research tool was used basically to capture the level of awareness, interest, readiness, and perception of Nigerian organisations towards telecommuting. A total of 180 questionnaires was administered to 180 Nigerian firms in Lagos, 120 questionnaires were counted valid for analysis. This study observed high level of awareness among Nigerian organisations but paradoxically, this high level of awareness does not engender the adoption of telecommuting by those organisations. Findings revealed that the fright of difficulty in assessing employees’ performance, inadequacy of ICT infrastructures and the fear of corporate data theft are the key factors inhibiting the adoption of telecommuting by organisations. This study concluded there is a need for organisations to be aware of the benefits of telecommuting and how telecommuting policy can be devised to strategically fit into the work culture for productivity. Keywords: Telecommuting; Public Research Institutes, Adoption, Factors, Lagos.